2017
DOI: 10.1038/s41598-017-01695-3
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic microRNA profile associated with coronary collateral artery function in chronic total occlusion patients

Abstract: An expansive collateral artery network is correlated with improved survival in case of adverse cardiac episodes. We aimed to identify cellular microRNAs (miRNA; miR) important for collateral artery growth. Chronic total occlusion (CTO) patients (n = 26) were dichotomized using pressure-derived collateral flow index (CFIp) measurements; high collateral capacity (CFIp > 0.39; n = 14) and low collateral (CFIp < 0.39; n = 12) capacity. MiRNA profiling via next generation sequencing from various monocyte phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A detailed description of the patient’s and healthy individual’s characteristics is given in Table 1 . Selection of miRNAs was first conducted by careful in silico analysis, studying the literature for relevant miRs associated with MI 16 , 21 , 22 . We also screened for miRNAs related to cardiovascular pathogenesis including endothelial injury, endothelial activation, and vascular inflammation 21 .…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the patient’s and healthy individual’s characteristics is given in Table 1 . Selection of miRNAs was first conducted by careful in silico analysis, studying the literature for relevant miRs associated with MI 16 , 21 , 22 . We also screened for miRNAs related to cardiovascular pathogenesis including endothelial injury, endothelial activation, and vascular inflammation 21 .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a recent study has found that blood monocytes in patients with developed collateral are remarkably lower than those in patients with poor collateral and an increased lymphocyte/monocyte ratio predicts well‐developed coronary collateral . In chronic occlusion patients, the expression of miRNA339‐5p in monocytes of low collateral capacity patients is significantly decreased . Hence, it may be inferred that monocyte or its relevant factors are the potential markers of good/poor collateral.…”
Section: Discussionmentioning
confidence: 99%
“…61 In chronic occlusion patients, the expression of miRNA339-5p in monocytes of low collateral capacity patients is significantly decreased. 62 Hence, it may be inferred that monocyte or its relevant factors are the potential markers of good/ poor collateral.…”
Section: Con Cluding Remark Smentioning
confidence: 99%
“…However, we found that patients with CTO had signi cantly higher risk of recurrent myocardial infarction when compared with those patients without CTO. Therefore, CTO is not only a risk factor for the one-year death of patients with multivessel disease [13][14][15] , but also a risk factor for recurrent myocardial infarction within ve years.…”
Section: Discussionmentioning
confidence: 99%